miRNA, lncRNA and circRNA: Targeted Molecules Full of Therapeutic Prospects in the Development of Diabetic Retinopathy - Chang, Xingyu; Zhu, Guomao; Cai, Zongyan; Wang, Yaqi; Lian, Rongna; Tang, Xulei; Ma, Chengxu; Fu, Songbo (Frontiers in Endocrinology, 2021)
Diabetic retinopathy is a common diabetic complication and the main cause of blindness worldwide, seriously affecting the quality of life of patients. Studies have shown that non-coding RNA has distinct differentiated expression in DR and plays an important role in the occurrence and development of DR. Non-coding RNAs represented by microRNA (miRNA), LncRNA (LncRNA) and CircRNA (CircRNA) have been shown to be widely involved in the regulation of gene expression and affect multiple biological processes of retinopathy. This article will review the three RNAs related to the occurrence and development of DR on the basis of previous studies, especially their effects on retinal microangiopathy, retinal pigment epithelial cells, and retinal nerve cells, and discuss their underlying mechanisms and connections. Overall, the review will help us understand more about the role of non-coding RNA in the occurrence and development of DR, and provide ideas for exploring potential therapeutic directions and targets.